Students' attitude and satisfaction living in sustainable on-campus hostel - Norazah Mohd Suki; Iftekhar Amin Chowdhury (Penerbit Universiti Malaysia Sabah, 2015)
This research aims to investigate whether location, facilities and quality of on-campus hostels affect students’ attitude living in on-campus hostels and their satisfaction with hostel life. Next, relationship between students’ attitude and their satisfaction with hostel life are also examined. Data were collected from 230 students living in on-campus hostels in a public higher learning institution in the Federal Territory of Labuan, Malaysia. Empirical results via multiple regressions discovered that students’ satisfaction living in hostels is only affected by hostels quality, except for hostels location and hostels facilities. Students are very concerned that the floor be covered with tile, and the plumbing system be perfect with no water problems which affect their satisfaction living in hostels. Further investigation of the study recognized that students’ attitude is strongly affected by satisfaction followed by hostel facilities. This study provides strong evidence that could help the student housing administrators and the university hostel management and other accommodation services to better understand the customer satisfaction with the service delivery by identifying the significant factors in determining student satisfaction and improving the performance of university hostels towards meeting the satisfaction of students by providing highquality living environments. Direction for future research is also exemplified.